ANALISIS FAKTOR DOMINAN YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PRODUK MAKANAN HALAL DI KOTA LHOKSEUMAWE - Intan Cahyani Rachman (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to analyze the factors influencing the purchase intention of halal food products among the Muslim community in Lhokseumawe City. A quantitative approach was employed by distributing questionnaires to 100 respondents aged over 15 years. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationships among latent variables, namely halal awareness, product quality, price perception, brand image, and purchase intention. The results revealed that halal awareness or attitude does not significantly influence purchase intention, whereas product quality, price perception, and brand image showed significant effects. These findings indicate that external factors play a more dominant role in encouraging consumers to purchase halal products. Therefore, effective marketing strategies should integrate religious values with competitive pricing, high product quality, and a strong brand image to boost consumer interest in halal products.